Pregnant women utilization of dental services: still a challenge in low resource setting - Chidozie Onwuka; Chidinma Ifechi Onwuka; Emeka Ifeanyi Iloghalu; Peter Chukwudi Udealor; Euzebus Chinonye Ezugwu; Ifeanyi Emmanuel Menuba; Emmanuel Onyebuchi Ugwu; Chinyere Ututu (BMC, 2021)
Abstract Background Poor oral health in pregnancy can be associated with poor pregnancy outcome, however, dental consultation among pregnant women appears to be low. Methods This was a questionnaire-based study of 413 women who attended the antenatal clinic of University of Nigeria Teaching Hospital (UNTH), Ituku/Ozalla, Enugu. The information obtained was analyzed using SPSS version 22. A p-value of less than 0.05 was considered statistically significant. Results Only 36 (8.7%) of the respondents had dental consultations in index pregnancy for complaints such as tooth ache and decay (66.7%) and pain as well as swelling of the gum (33.3%). The most common reason given for not visiting a dentist during the index pregnancy was the visit not being relevant to their pregnancy outcome (69.2%). After counseling them, only 249 (60.3%) agreed to have dental consultation during subsequent pregnancies. The relationship between visiting the dentist and place of residence (< 0.001), occupation (0.019) and frequency of brushing/ changing of brush (0.005, < 0.001 respectively) were statistically significant. Conclusion The prevalence of dental consultation during pregnancy is very low. Pregnant women should be encouraged to have routine dental consultation with oral health counseling and check-up incorporated as part of routine antenatal care.